Work measurement - Whitmore, Dennis A. (London : Heinemann, 1975)
This book is here presented in a major new treatment, dealing in depth with the basic concepts, techniques, and practical applications of the subject. It is a definitive text that will become a volume of permanent reference on all aspects of this vitally important topic.
Published on behalf of the Institute of Practitioners in work study, Organisation and methods.
Includes bibliographical references p. 417-430 and index.
hza 25/07/2018
Loans
Keywords: Work measurement; Productivity; Management